THE IMPACT OF THE APRIL 1848 LAWS ON THE TRANSFORMATION OF SOCIETY, OR THE ABOLITION OF SERFDOM - Szentpáli-Gavallér, Pál (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
Abstract: The study describes the development of serfdom, the Dózsa uprising, which was caused by social conflicts and the limitation of serfdom and their legal consequences. A significant milestone was the Urbárium of 1767, followed by two other decisive dates: the Revolution of 1848 and the Compromise of 1867. The latter was also significant in that it paved the way for the Austro-Hungarian Empire (alongside Japan) to enter the First World War, in parallel with and in a similar way to the Meiji Restoration, which began in Japan in 1867–1868. The study outlines the relations between serfdom and the peasantry, not only from a legal-historical, but also from an economic and social-historical perspective.